The role of oxygen in the process of modifying the state functionals of wheat seeds and lactobacilli by an electromagnetic field - Kovalenko, O.I.; Kalinichenko, S.V.; Skiyar, N.I.; Kulish, S.M.; Levchenko, V.M.; Antusheva, T.I. (Radiotekhnika, 2024)
The possibilities to modify the functional characteristics of wheat seeds and lactobacilli using low-intensity electromagnetic fields (EMF) in frequency ranges associated with gas resonances are considered. The objective of the work is to study the role of oxygen in the process of modifying the functional indicators of soft wheat seeds and lactobacilli strains state irradiating them with low-intensity EMF on the resonant absorption lines of oxygen, hydrogen and ozone, additionally enriching water with oxygen during its irradiation and subsequent soaking of seeds in it, and creating conditions for cultivating bacteria in an environment with normal and reduced oxygen content. To carry out electromagnetic effect, generators G4-141 and G4-142 were used. The enrichment of water with oxygen occurred during its irradiation with EMF, after which wheat seeds were soaked in it. Microaerophilic conditions for the cultivation of bacteria in microanaerostats. The role of oxygen influence on the vital activity of biological objects of different classes (wheat seeds and lactobacilli) is shown. The possibility of stimulating seed germination by indirect irradiation with oxygen-enriched water at the 61,0 GHz oxygen resonance absorption line with a short exposure of the signal is shown. It has been found that by irradiating lactobacilli in the frequency ranges of 42,2 and 61,0 GHz, they can stimulate their absorption of glucose when cultivated under aerobic conditions, which, in turn, helps to increase the rate of population development. The conditions under which increasing production of high molecular weight peptide fractions (presumably plantaricins) by L. Plantarum strain and decreasing the share of low molecular weight proteins in the nutrient medium occur, which indicates, accordingly, an increasing the antagonistic activity of the L. plantarum strain and an improvement in its absorption of nutrients, were defined. The results obtained open up the prospect of using electromagnetic technologies in agriculture when preparing seeds for sowing and in medicine, in particular in the development of new generation drugs based on lactobacilli with increased colonization and antagonistic properties towards pathogens.